JUSTIFICATION AND DEVELOPMENT OF A MODEL FOR IMPROVING LEGAL LITERACY IN PRESCHOOL EDUCATION INSTITUTION DIRECTORS (American Journal of Interdisciplinary Research and Development, 2025)
This article substantiates the relevance and necessity of developing the legal literacy of preschool education institution (PEI) directors. It also highlights the theoretical and practical significance of creating a modern model aimed at enhancing the legal knowledge of PEI directors. The article presents key principles, stages, and methods of developing legal literacy, as well as the structural components and expected outcomes of the proposed model.